KONSEP TAWAKAL DALAM PENDIDIKAN ISLAM (Studi Analisis Kitab Ta’lim Muta’allim Karya Syekh Az-Zarnuji) - Rusli, Fiki Khapipah; Masturoh, Imas; Hayatunnufus, Alifa Baiduri (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2015)
This research was conducted to explore the concept of tawakal in Islamic education contained in the Mutaallim Ta'lim book. This study yields the following conclusions: 1) The concept of tawakal in Islamic education according to Sheikh Az-Zarnuji is explained in the seventh chapter. The concept of tawakal in this book is devoted to students in their activities seeking knowledge. The tawakal context that is explained is that to all knowledge seekers or students in seeking knowledge should not be focused on the rizki affairs of either mind, heart or body, because indeed anyone who seeks knowledge, especially the science of Islamic education and he understands it, will be opened by Allah for him from unexpected road. 2) The implications of the concept of tawakal in Islamic education according to the Ta'lim Muta'allim book by Sheikh Az-Zarnuji on Indonesian education are all factors supporting education both formal and non-formal education must always try to supervise and foster the morality of students as long as they seek knowledge so that no deviations in character and goals from Indonesian national education can be realized.